Newborn screening for lysosomal storage disorders by tandem mass spectrometry in North East Italy. Issue 2 (15th November 2017) - Burlina, Alberto B.; Polo, Giulia; Salviati, Leonardo; Duro, Giovanni; Zizzo, Carmela; Dardis, Andrea; Bembi, Bruno; Cazzorla, Chiara; Rubert, Laura; Zordan, Roberta; Desnick, Robert J.; Burlina, Alessandro P.
Abstract: Background: Lysosomal storage diseases (LSDs) are inborn errors of metabolism resulting from 50 different inherited disorders. The increasing availability of treatments and the importance of early intervention have stimulated newborn screening (NBS) to diagnose LSDs and permit early intervention to prevent irreversible impairment or severe disability. We present our experience screening newborns in North East Italy to identify neonates with Mucopolysaccharidosis type I (MPS I) and Pompe, Fabry, and Gaucher diseases. Methods: Activities of acid β‐glucocerebrosidase (ABG; Gaucher), acid α‐glucosidase (GAA; Pompe), acid α‐galactosidase (GLA; Fabry), and acid α‐L‐iduronidase (IDUA; MPS‐I) in dried blood spots (DBS) from all newborns during a 17‐month period were determined by multiplexed tandem mass spectrometry (MS/MS) using the NeoLSD ® assay system. Enzymatic activity cutoff values were determined from 3500 anonymous newborn DBS. In the screening study, samples were retested if the value was below cutoff and a second spot was requested, with referral for confirmatory testing and medical evaluation if a low value was obtained. Results: From September 2015 to January 2017, 44, 411 newborns were screened for the four LSDs. We recalled 40 neonates (0.09%) for collection of a second DBS. Low activity was confirmed in 20, who had confirmatory testing. Ten of 20 had pathogenic mutations: two Pompe, two Gaucher, five Fabry, and one MPS‐I. The incidences of Pompe and Gaucher diseases were similar (1/22, 205), with Fabry disease the most frequent (1/8882) and MPS‐I the rarest (1/44411). The combined incidence of the four disorders was 1/4411 births. Conclusions: Simultaneously determining multiple enzyme activities by MS/MS, with a focus on specific biochemical markers, successfully detected newborns with LSDs. The high incidence of these disorders supports this screening program.